EFEK PENAMBAHAN FOOT CORE STABILITY EXERCISE PADA INTERVENSI CORE STABILITY EXERCISE DALAM PENINGKATAN POSTURAL CONTROL PASIEN PASCASTROKE - Sondang Samosir; Jerry Maratis; Kesit Ivanali (LPPM Universitas Abdurrab, 2024)
Objective: to analyze the improvement of postural control of post-stroke patients due to the addition of foot core stability to core stability exercise. Method: the implementation of this study is a type of